Nanotechnology, additive manufacturing and genius loci. A case of jewellery design - Debora Puglia; Benedetta Terenzi (Agathón)
The presented research aims to spread the knowledge of regional excellence through the design of a series of jewels that highlight its Made in Umbria origin, enhancing in an unprecedented way the tangible and intangible riches of the territory. The work shows the possibilities of innovation that arise from the overall strategy of a Territorial Design project by working, on the one hand, on the definition of the peculiarities of the natural and man-made environment, in terms of creativity and aesthetic expression, on the other hand, on the use of nanotechnology to facilitate a conscious use of resources (local waste materials and biopolymers) in combination with the possibilities offered by additive manufacturing.